Mrs. Earl Dailey at the 1973 YWCA annual meeting - Unknown:::Creator::::::::::::
Photograph shows Mrs. Earl (Mae) Dailey (right) and another woman at a YWCA annual meeting. They are both dressed nicely and wearing corsages. There is a bulletin board behind them with the items on it placed so that they spell out YWCA. The headings on the bulletin board read: "In the beginning" and "End of an era - YWCA." They are attending the 1973 YWCA annual meeting.